2016
DOI: 10.1177/1350650116642098
|View full text |Cite
|
Sign up to set email alerts
|

Aerostatic thrust bearing performances analysis considering the fluid-structure coupling effect

Abstract: This article presents a novel calculation method for the bearing performance of the aerostatic thrust bearing. This method is provided while taking the fluid-structure coupling effect into account. High pressure air film leads to the structure deformation, thus the bearing clearance after deformation is utilized to estimate the real bearing performance. Furthermore, the influencing factors on the bearing performance, the thrust plate's thickness, and the orifices' location, are investigated on the basis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In order to investigate the convergence characteristics of the FDFI method, we choose the following parameters: the bearing diameters R 1 =75 mm, R 2 =50 mm, and R 0 =62.5 mm, and a row is arranged with eight orifices, the diameter of the orifice d = 0.2 mm, the average clearance h 0 =20 μm, the supply pressure p 0 =0.5 MPa, the rotational speed ω = 0, and the eccentricity ratio ɛ = 0.2. The convergence condition is set to E ≤ 10 −6 . Figure 7 shows the pressure distribution under the above conditions.…”
Section: Convergence Characteristics Of the Fdfi Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate the convergence characteristics of the FDFI method, we choose the following parameters: the bearing diameters R 1 =75 mm, R 2 =50 mm, and R 0 =62.5 mm, and a row is arranged with eight orifices, the diameter of the orifice d = 0.2 mm, the average clearance h 0 =20 μm, the supply pressure p 0 =0.5 MPa, the rotational speed ω = 0, and the eccentricity ratio ɛ = 0.2. The convergence condition is set to E ≤ 10 −6 . Figure 7 shows the pressure distribution under the above conditions.…”
Section: Convergence Characteristics Of the Fdfi Methodsmentioning
confidence: 99%
“…Lu et al. 6 provided a calculation method for the performance of aerostatic thrust bearings, which took the fluid–structure coupling effect into account. Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al. 7 presented a novel calculation method for the bearing performance of the aerostatic thrust bearing, and the influencing factors on the bearing performance, the thrust plate’s thickness, and the orifices’ location were investigated on the basis of the fluid–structure coupling effect.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous researches theoretically and experimentally studied the static performance of aerostatic spindle with consideration of FSI effect. 16,17 It indicated that the thickness of thrust plate affects the performance of aerostatic spindle greatly. If its thickness is too thin, the air film force could result in large deformation of thrust plate and lower the static performance of aerostatic bearing.…”
Section: Introductionmentioning
confidence: 99%